Aging and Aneurysms: Case Report of Moyamoya Disease in an Elderly Man (Nepalese Journal of Radiology, 2025)
Moyamoya disease is a chronic veno-occlusive disorder characterized by the progressive stenosis of the intracranial internal carotid artery and its proximal branches, leading to the formation of fragile collaterals. It exhibits a bimodal distribution, with patients typically presenting in early childhood and middle age. Presentations include ischemia or intracranial hemorrhage, and it is rarely seen in the elderly population. We present a case of an elderly male who presented with an intracranial hemorrhage.